Process optimisation for production of value added products from pummelo (citrus grandis (L) osbeck) - Suja G Nair (Department of Processing Technology, College of Horticulture, 2006)
Pummelo (Citrus grandis (L.) Osbeck) is an important member of the citrus genus. The fruit is rich in vitamin C and has many medicinal properties. A major chunk of production of this fruit is being wasted due to the lack of scientific handling and processing technologies. In this context, the present investigation “Process optimisation for production of value added products from Pummelo (Citrus grandis (L.) Osbeck)” was taken up to standardise technologies for processing and value addition of pummelo. The ideal stage for harvesting pummelo fruits in Kerala was found to be seventh month after fruit set. At this stage the fruits attain maximum size with high juice content, TSS and ascorbic acid content. The acidity of the fruits at this stage was low. The fallen fruits at the same stage were found to be inferior in quality. Out of 12 accessions of pummelo analysed for their processing characters, AC. 3 collected from Kottayam and AC. 11 collected from Thrissur were selected out based on their merits with respect to size, juice content, TSS and ascorbic acid content. In general, the accessions collected from Kottayam were superior to those collected from Ernakulam and Thrissur. Similarly the selections from IIHR, Bangalore were superior to those collected from Kerala. The study could bring out an ideal process for easy peeling of pummelo segments. Dipping the segments in 15 per cent brine for 15 minutes and then steaming for 15 minutes was found to be the most effective method. The quality of the juice extracted from the segments after this treatment did not vary much from that of fresh hand extracted juice. Osmo extraction (by mixing the juice vesicles with 30 per cent sugar and incubating for 3 hrs.) was found to be a better method for juice extraction from the peeled segments. The quality of the juice extracted through this method was comparatively better. Crushing in mixie and screw pressing yielded low quality juice. Addition of sucrose at 30 per cent level was found to mask the bitterness in juice. Addition of pectin and pectinase and increasing the pH of the juice did not give valuable results. Blending pummelo juice with orange juice at 70: 30 per cent level was good as this combination was scored to be highly acceptable with respect to colour, taste and overall acceptability. The sweetened juice prepared with this ideally blended juice, adding with 30 per cent sugar gained comparatively good score. The squash prepared with sweetened pummelo juice blended with orange juice at 70: 30 proportion was found to be acceptable. The pummelo based RTS was not found as a good product. The studies done on value addition have shown that it is better to prepare the beverages with pummelo juice blended with orange juice than using pummelo juice alone.